Comprehensive deciphering prophages in genus Acetobacter on the ecology, genomic features, toxin–antitoxin system, and linkage with CRISPR-Cas system - Qian, Chenggong; Ma, Jiawen; Liang, Jiale; Zhang, Lei; Liang, Xinle (Frontiers in Microbiology, 2022)
Acetobacter is the predominant microbe in vinegar production, especially in those natural fermentation achieved by complex microbial community. Co-evolution of prophages with Acetobacter including integration, release, and dissemination heavily affects the genome stability and production performance of industrial strains. However, little has been discussed yet about prophages in Acetobacter. Here, prophage prediction analysis using 148 available genomes from 34 Acetobacter species was carried out. And, the type II toxin-antitoxin systems (TAs) and CRISPR-Cas systems encoded by prophages or in the chromosome were analyzed. Totally, 12,000 prophage fragments were found, of which 350 putatively active prophages were identified in 86.5% of the selected genomes. Most of active prophages (83.4%) belonged to the order Caudovirales dominated by the families Siphoviridae and Myroviridae prophages (71.4%). Notably, Acetobacter strains survived in complex environments frequently carried multiple prophages compared with that in restricted habits. Acetobacter prophages showed high genome diversity and horizontal gene transfer across different bacterial species by genomic features characterization, average nucleotide identity (ANI), and gene structure visualization analyses. About 31.14% of prophages carrying type II TAS, suggesting its important roles such as addiction, bacterial defense, and growth-associated bioprocesses to prophages and hosts. Intriguingly, the genes coding for Cse1, Cse2, Cse3, Cse4, and Cas5e involved in type I-E and Csy4 involved in type I-F CRISPR arrays were firstly found in two prophages. Type II-C CRISPR-Cas system existed only in Acetobacter aceti, while the other Acetobacter species harbored the intact or eroded type I CRISPR-Cas systems. Totally, the results of this study provide fundamental clues for future studies towards the role of prophages on the cell physiology and environmental behavior of Acetobacter.